2005
DOI: 10.1111/j.1601-0825.2005.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus anginosus infection in oral cancer and its infection route

Abstract: Infection of S. anginosus could occur frequently in oral squamous cell carcinoma and that dental plaque could be a dominant reservoir of the S. anginosus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 33 publications
6
79
1
1
Order By: Relevance
“…S. anginosus is an opportunistic pathogen and forms part of the normal flora in the human oral cavity, genitourinary tract, and gastrointestinal tract (3), and it is generally considered to have a relatively low pathogenic potential compared with other streptococci, in particular members of the pyogenic species group. However, S. anginosus is increasingly being recognized as being able to cause a wide range of purulent infections that commonly manifest as abscess formation, and its presence has also been detected in esophageal cancer (4)(5)(6)(7)(8)(9). Despite the increased awareness of the clinical importance of S. anginosus, the molecular basis of pathogenicity of this species has not been determined.…”
mentioning
confidence: 99%
“…S. anginosus is an opportunistic pathogen and forms part of the normal flora in the human oral cavity, genitourinary tract, and gastrointestinal tract (3), and it is generally considered to have a relatively low pathogenic potential compared with other streptococci, in particular members of the pyogenic species group. However, S. anginosus is increasingly being recognized as being able to cause a wide range of purulent infections that commonly manifest as abscess formation, and its presence has also been detected in esophageal cancer (4)(5)(6)(7)(8)(9). Despite the increased awareness of the clinical importance of S. anginosus, the molecular basis of pathogenicity of this species has not been determined.…”
mentioning
confidence: 99%
“…Infecção por Candida tem sido associada com desenvolvimento de câncer na cavidade bucal desde que foi encontrada como causa de leucoplasia bucal e correlacionada com displasia bucal epitelial 8 . Tem-se sugerido que o biofilme dental poderia atuar como um reservatório de S. anginosus que parece frequentemente infectar carcinomas bucais e esofágicos 42 . A sugestão de que bactérias bucais podem passar por meio do tecido mucoso para dentro de uma massa tumoral não é surpreendente; bactérias originadas da boca têm previamente sido apresentadas, infectando sistemicamente e podem translocar para dentro de linfonodos 43 .…”
Section: Discussionunclassified
“…S. anginosus ex ists only in dental plaques and cannot be detected in saliva. Sasaki et al [19] discovered high incidence of bacterial infection in patients with oral squamous cell carcinoma, and patients with S. anginosus detected in canceration position were also diagnosed with oral squamous cell carcinoma, which showed the same genotype of S. anginosus in squamous cell carcinoma region similar to that in dental plaques.…”
Section: Relationship Between Oral Microorganisms and Oral Squamous Cmentioning
confidence: 99%
“…Sasaki et al [19] observed that oral Streptococcus infection can induce synthesis of nitric oxide and cyclooxygenase-2, increase DNA damage, and promote occurrence of oral cancer. Some bacterial toxins can also interfere with signal transduction of cells and promote occurrence of tumors.…”
Section: N F L U E Nc E O F O R a L M Ic R O O R G A N I S M S A Ndmentioning
confidence: 99%